PENGARUH MINUMAN KOMBUCHA SALAK SIDEMPUAN TERHADAP KADAR HDL DAN LDL PADA TIKUS DIET TINGGI LEMAK - Salsabila Khalda; Isra Thristy (Fakultas Kedokteran Universitas Islam Sumatera Utara, 2026)
Dyslipidemia is a metabolic disorder characterized by continuous alterations in plasma lipid levels. Kombucha, a fermented beverage produced from sweetened tea using SCOBY, has been reported to lower cholesterol levels. Research on kombucha continues to expand, particularly regarding the use of non-tea substrates for fermentation, such as salak fruit. This study aimed to analyze the effect of Sidempuan salak kombucha on HDL and LDL levels in male rats (Rattus norvegicus) induced with a high-fat diet. A true experimental method with a posttest-only control group design was employed, involving 32 rats divided into four groups: KN (standard feed for 6 weeks), K− (standard feed + high-fat diet for 6 weeks), P1 (standard feed + high-fat diet + 2.7 ml/day Sidempuan salak kombucha for 6 weeks), and P2 (standard feed + high-fat diet + 5.4 ml/day Sidempuan salak kombucha for 6 weeks). The collected data were analyzed using a One-Way ANOVA test. The results showed no significant differences in HDL and LDL levels among the four groups (p > 0.05). In conclusion, the administration of Sidempuan salak kombucha did not produce a significant effect on HDL and LDL levels in male rats induced with a high-fat diet.